PELAKSANAAN TAQNIN AL-AHKAM DI NEGARA KESATUAN REPUBLIK INDONESIA - Husni Husni; Hasanuddin Hasanuddin (SYARIAH: Journal of Islamic Law, 2021)
Qanun al-Ahkam is basically an attempt to choose a more beneficial opinion about a law in a certain country and time which is considered to have greater maslahat power for the benefit of the wider community. The purpose of this paper is to find out how the implementation of taqnin al-ahkam in the Republic of Indonesia. The results of this study say that taqnin al-Ahkam can be implemented through the legislative process. Namely the process of making law and legal products. In this case, Islamic law which is sourced from revelation is then compiled in a law that has binding power for all citizens so as to minimize the gap between Islamic law that develops and is understood as Islamic teachings and law in practice.